2008
DOI: 10.1152/ajpcell.00612.2006
|View full text |Cite
|
Sign up to set email alerts
|

Vesicular localization of the rat ATP-binding cassette half-transporter rAbcb6

Abstract: The clarification of subcellular localization represents an important basis toward characterization of ATP-binding cassette (ABC) transporters and resolution of their roles in cellular physiology. Rat Abcb6 (rAbcb6) is a membrane-situated half-transporter belonging to the ABC protein superfamily. To investigate rAbcb6 subcellular distribution, the human colon adenocarcinoma line LoVo, which we found to be devoid of endogenous human ABCB6 mRNA, was employed for heterologous expression of rAbcb6 bearing a COOH-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…Since the mutations did not compromise overall expression levels, we analyzed the localization of ABCB6 variants in intracellular compartments using confocal microscopy. While initial reports indicated localization of ABCB6 in the outer mitochondrial membrane [7], [9], more recent studies detected ABCB6 in the plasma membrane [9], the Golgi apparatus [10], and in organelles of the vesicular system [11], [12], [13], [14], [15]. In line with the reports demonstrating the endolysosomal localization of ABCB6, our HA-tagged ABCB6 construct appeared in the lysosomal compartment of Hela cells, and not in the mitochondria (Figure 4).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Since the mutations did not compromise overall expression levels, we analyzed the localization of ABCB6 variants in intracellular compartments using confocal microscopy. While initial reports indicated localization of ABCB6 in the outer mitochondrial membrane [7], [9], more recent studies detected ABCB6 in the plasma membrane [9], the Golgi apparatus [10], and in organelles of the vesicular system [11], [12], [13], [14], [15]. In line with the reports demonstrating the endolysosomal localization of ABCB6, our HA-tagged ABCB6 construct appeared in the lysosomal compartment of Hela cells, and not in the mitochondria (Figure 4).…”
Section: Resultssupporting
confidence: 88%
“…Although initial findings suggested that loss of one Abcb6 allele in embryonic stem (ES) cells impairs porphyrin synthesis, mice derived from these stem cells were phenotypically normal [8]. Recent studies have challenged the paradigm linking the function of ABCB6 to mitochondria, and suggested that ABCB6 is localized in the endolysosomal continuum including the plasma membrane [9], the Golgi apparatus [10], and organelles of the vesicular system [11], [12], [13], [14]. ABCB6 is upregulated during erythroid differentiation, and although a proportion is lost during reticulocyte maturation through secreted exosomes, ABCB6 is expressed in mature red blood cells at relatively high levels [15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Cpabc7 is 3 times more highly expressed in the Malpighian tubules than in the gut. Cp ABC7 is most homologous to the human ABCB6 (Figure 3) which is reported to be localized in the Golgi apparatus [124], mitochondria, plasma membranes [125], vesicular structures [126], or endolysosomes and lysosomes of cells [79]. ABCB6 is discussed to play a role in the heme metabolism [78], [127][129], in the drug and arsenite resistance of cells [130][132].…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, several studies have shown that ABCB6 is also located in the plasma membrane, ER and Golgi apparatus (as part of the secretory pathway) [41,43,65,82,85]. It was also shown that certain mutations in ABCB6 might cause an ocular disease named coloboma in humans [85].…”
Section: Understanding Abcb10 Function By Phylogenetic Comparison:mentioning
confidence: 99%